1) f(x) = x²
f'(x) = 2x
2) f(x) = √3/2 * x³ - x
f'(x) = 3√3/2 * x² - 1
3) f(x) = -√3/3 * x⁵ - 0,5 - 1,5*x⁴
f'(x) = -5√3/3 * x⁴ - 6x³
4) f(x) = (2x + 3)³
f'(x) = 3*2*(2x+3)² = 6(2x+3)²
5) f(x) = √(x² - 3)
f'(x) = 0,5*2x/√(x²-3) = x/√(x²-3)
Пошаговое объяснение:
а). 8 7 2 26 204
б). а). + -1 0
в). а). + б). + 0.(202) 3/19 15/3
2.1
(5,74+8,27)-(3,4+3,78)=6,83
1) 5,74+8,27=14,01
2) 3,4+3,78=7,18
3) 14,01-7,18=6,83
63 см = 6 дм 3см, 400см= 4 м, 223см= 2м 20 дм 3 см
У меня в кошельке было 432 рубля мой одноклассник уранил свой кошелёк в котором 343 рубля сколько теперь у меня?